Two point diagonally block method for solving boundary value problems with Robin boundary conditions - Abdul Majid, Zanariah; Mohd Nasir, Nadirah; Ismail, Fudziah; Bachok @ Lati, Norfifah (Universiti Putra Malaysia Press, 2019)
This numerical study emphasizes on fifth order multistep block method for solving second order boundary value problems (BVPs) imposing Robin boundary conditions. The shooting technique will be utilized to compute the approximate solutions at two point simultaneously. The implementation of predictor-corrector scheme follows the P E(CE) r mode. Numerical results are presented to give a clear view of the performances for the propose method. The order and stability of the method are also discussed.